PHRASEOSYNTACTIC SCHEMES WITH OPPOSITE MEANINGS IN THE GERMAN LANGUAGE (Proceedings of Southern Federal University. Philology, 2013)
Ostrikova G.N.Keywords: opposite meanings, phraseosyntactic scheme, nominative and emotional-evaluative enantiosemy.The article describes the phraseoschemes with opposite meanings in German. The author identifies and studies enantiosemic phraseoschemes with the meaning of “affirmation/negation” and phraseoschemes with the meaning of “evaluation”. We can distinguish nominative and emotional-evaluative enantiosemy, as well as symmetrical and asymmetric enantiosemy. The most productive in the aspect of enantiosemy are evaluative phraseoschemes due to the specific meaning of emotional evaluation, which is characterized by a large number of tones and variants.